Chemical binding of inorganic flame retardant compositions to polyamide fibers - Krival’ Денис; Reva Ольга (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
The investigation of the dependence of the strength of binding of inorganic non-toxic flame retardant compositions to the surface of polyamide fibres on the conditions of step impregnation processing. A method of chemical binding of inorganic modifier to the polyamide, the composition of the etching solutions, providing the fixation of the maximum amount of flame retardant on polyamide fiber.